DAKWAH DAN POLA RELASI GENDER Analisis Pengembangan Pola Relasi Gender Melalui Aktivitas Dakwah Majelis Taklim dan Implementasinya pada Kelurga Muslim Di Kecamatan Tampan Pekanbaru - Ginda Ginda (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2011)
Majelis Taklim one of mission form already admitted goverment dan society. Activity accuses at Majelis Taklim is of important in smartens up society. Notably deep tutorial Islam knowledge. Contribution missionarizes Majelis Taklim to gender relationship grasp good Moslem. Muslem society sees about man and women relationship correspond to Majelis Taklim grasp. Found observational result that Majelis Taklim potential was made to building genders relationship.